Developing A 4C-Based English Supplementary Material: A Balinese Tourism Vocational School Context - Widiastuti, Ida Ayu Made Sri; Utami , IGA. Lokita Purnamika (Journal of English Education and Teaching, 2025)
Currently, English teaching and learning in vocational high schools increasingly incorporates 4C skills—critical thinking, communication, collaboration, and creativity—into the teaching and learning process. The study aims to outline the development of English supplementary materials for eleventh-grade tourism service business students at a state vocational school in Bali, and assess the quality of these materials. Conducted as Design and Development (D&D) research, the study follows the ADDE (Analysis, Design, Development, and Evaluation) model. Utilizing various instruments such as observation sheets, interview guides, syllabus analysis matrices, supplementary material blueprints, resource sheets, and judgment rubrics, the research identified a seven-step development process: (1) material identification; (2) activity identification for 4C skills reinforcement; (3) element and picture sourcing; (4) Activity integration with Engaging Platforms; (5) combination of materials, activities, and elements into book content; (6) book cover design; and (7) layout finalization. The developed product was rated as "excellent" by two experts, and both teachers and students found the supplementary materials effective in enhancing 4C skills. The findings imply that well-structured supplementary materials can foster essential 21st-century skills among students. Moreover, this study shows that the incorporation of 4C skills into English supplementary materials potentially enhances not only students' language proficiency but also critical thinking abilities.